Artificially altered gravity elicits cell homeostasis imbalance in planarian worms, and cerium oxide nanoparticles counteract this effect. Issue 11 (7th May 2021) - Salvetti, Alessandra; Degl'Innocenti, Andrea; Gambino, Gaetana; van Loon, Jack J.W.A.; Ippolito, Chiara; Ghelardoni, Sandra; Ghigo, Eric; Leoncino, Luca; Prato, Mirko; Rossi, Leonardo; Ciofani, Gianni
Abstract: Gravity alterations elicit complex and mostly detrimental effects on biological systems. Among these, a prominent role is occupied by oxidative stress, with consequences for tissue homeostasis and development. Studies in altered gravity are relevant for both Earth and space biomedicine, but their implementation using whole organisms is often troublesome. Here we utilize planarians, simple worm model for stem cell and regeneration biology, to characterize the pathogenic mechanisms brought by artificial gravity alterations. In particular, we provide a comprehensive evaluation of molecular responses in intact and regenerating specimens, and demonstrate a protective action from the space‐apt for nanotechnological antioxidant cerium oxide nanoparticles.